To kill a mockingbird - Lee, Harper (New York Grand Central Pub., 1982)
The conscience of a town steeped in prejudice, violence, and hypocrisy is pricked by the stamina and quiet heroism of one man's struggle for justice, in this Pulitzer Prize-winning classic that has been translated into more than 40 languages.
Keywords: Fathers and daughters -- Fiction; Race relations -- Fiction; Trials (Rape) -- Fiction; Girls -- Fiction; Southern States -- Fiction